Potential impacts of carbon pricing on vegetable cold chains - Oluwadara Alegbeleye; Kassie, G.T.; Ndour, A.; Muluken Elias Adamseged; Aruni Athukorala (Elsevier, 2025)
The urgent need to address climate change has prompted growing interest in carbon pricing mechanisms as tools for reducing emissions in food systems. This review explores how carbon pricing may affect vegetable cold chains, which rely on energy-intensive, temperature-controlled networks essential for preserving produce quality and limiting food loss. While carbon pricing can serve as an incentive for adopting energy-efficient technologies, renewable energy, and sustainable logistics practices, its implementation can also trigger adverse consequences. These include increased operational costs, potential disruptions to supply chains, food affordability challenges, and public health concerns, particularly for vulnerable populations. Drawing on global evidence, this paper discusses both the enabling conditions for carbon pricing (when applied to vegetable cold chains or relevant stages within them) to deliver environmental benefits and the risks of socio-economic trade-offs, including potential impacts on labour, equity, and food security. Mitigation strategies, such as revenue recycling, targeted subsidies, and hybrid policy designs, are also discussed. Overall, the paper emphasizes the need for carefully designed carbon pricing mechanisms tailored to the structure of vegetable cold chains to ensure a just and effective transition to low-carbon food systems.